Facial Myokymia With or Without Concurrent Neurological Deficits in Seven Dogs and Two Cats - Tomás Elvira; Claudia Mallol; Abbe Crawford; Edward Ives; Anne R. Fraser; Lorenzo Mari; Anna Tauro; Patricia Alvarez; Victoria Indzhova; Giulia Corsini; Bruno Lopes; Josep Brocal (Journal of Veterinary Internal Medicine)
ABSTRACT Background Myokymia is a form of peripheral nerve hyperexcitability that can be focal or generalized. Information regarding focal myokymia in veterinary medicine is currently limited, resulting in a need for a better understanding of this clinical sign. Hypothesis/Objectives Describe the clinical presentation, diagnostic findings, treatment, and outcomes in dogs and cats with facial myokymia (FM). Animals Seven dogs and two cats with clinically confirmed FM. Methods Retrospective study. Clinical records from six referral institutions were reviewed to identify cases with FM. Signalment, clinical presentation, diagnostic test results, treatment, and outcome were recorded and evaluated for each patient. Results Facial myokymia was detected before referral in 6/9 cases. Concurrent vestibular signs were present in 7/9 cases, whereas signs of facial nerve dysfunction other than FM were present in three cases. The diagnoses in the seven dogs were facial and vestibular neuropathy of unknown etiology (n = 2), extra‐axial neoplasia (n = 1), otitis media‐interna with intracranial extension (n = 1), otitis interna with associated facial and vestibulocochlear neuropathy (n = 1), meningoencephalitis of unknown origin (n = 1) and neoplasia or hypertrophic neuritis (n = 1). The two cats were diagnosed with retrobulbar adenosquamous carcinoma with intracranial extension and traumatic orofacial injury. When prednisolone was used (6/9 cases) FM improved or resolved, although relapses were common. Conclusions and Clinical Importance Facial myokymia is an uncommon and nonspecific clinical sign in dogs and cats, associated with a range of structural disorders affecting the facial motor nucleus, nerve, or both. Control of FM is variable, and treatment and outcome depend on the underlying cause.